Zeolite supplementation effects on lamb growth and gastrointestinal nematode infection, and economic analysis - Novita Esteves, Sérgio (Revista Ciência Agronômica, 2021)
Zeolite as a dietary supplement can improve animal resistance and resilience against gastrointestinal parasites. The effects of different levels of zeolite supplementation on gastrointestinal nematode infection, growth performance, and economic viability of male and female Santa Ines lambs were investigated. Four zeolite levels (0, 25, 50, and 75 g per day) were fed to 110 day-old animals in a randomized block experimental design. Eggs per gram of feces (EPG), total serum protein (TSP), and packed cell volume (PCV) were measured individually every week. The animals were weighed every 14 days and coprocultures were prepared. Male animals that reached an average live weight of 34 kg were harvested. The economic viability analysis of the experimental diets was based on feedlot periods of 56 and 91 days. Dietary supplementation with zeolite did not signifi cantly mitigate infections by nematodes and did not affect TSP, PCV, or feedlot lamb growth performance. Therefore, zeolite was not an effective (P > 0.05) dietary supplement for avoiding gastrointestinal nematode infection or improving growth performance. Male animals slaughtered after 56 days of feeding were more economically viable (P < 0.05) than those slaughtered after 91 days. Feedlotting demonstrated that male animals had superior performance (P < 0.05) and better economic (P < 0.05) results than female animals.